Ferroptosis-disulfidptosis-related CHMP6 is a clinico-immune target in colorectal cancer - Yifei Zhu; Huixia Huang; Jiayu Chen; Keji Chen; Yanxi Yao; Yaxian Wang; Yuxue Li; Zhibing Qiu; Dawei Li; Ping Wei (Biology Direct)
Abstract Background Ferroptosis and disulfidptosis are newly discovered forms of regulated cell death that play critical roles in cancer progression, metabolism, and immune evasion. However, their interplay and combined influence on colorectal cancer (CRC) progression remain insufficiently understood. Methods We developed a ferroptosis-disulfidptosis-related gene (FDRG) score using machine-learning algorithms to analyze gene modifications associated with these pathways in CRC, utilizing data from the TCGA and GEO databases. The model was externally validated, and associations with clinical outcomes, immune infiltration, mutational landscapes, immunotherapy responses, and drug sensitivity were explored. Key genes were further investigated through bioinformatics and in vitro experiments. Results We constructed an 8-gene risk model with strong prognostic value, stratifying CRC patients into high- and low-risk groups with significant differences in clinical characteristics, immune cell infiltration, and therapeutic responses. Among these genes, CHMP6 was identified as a previously uncharacterized tumor suppressor in CRC. Beyond its inhibitory effect on tumor cell proliferation, migration, and invasion, CHMP6 was found to play a critical role in modulating anti-tumor immunity. Our findings established CHMP6 as a dual-function tumor suppressor that not only restrains tumor progression but also enhances immune-mediated tumor control. Conclusions The FDRG score is a robust tool for predicting CRC prognosis, tumor microenvironment dynamics, and response to immunotherapy. CHMP6 emerged as a promising tumor suppressor and potential therapeutic target, offering new insights into CRC treatment strategies.